Kesalahan Penggunaan Kalimat Efektif dan Tanda Baca Dalam Teks Deskripsi Siswa Kelas VII SMP Jaya Negara Makassar - Nuzul Tenriana (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims (1) to describe the forms of errors in the use of effective sentences and punctuation in descriptive essays for class VII SMP Jaya Negara Makasar. (2) to interpret errors in the use of effective sentences and punctuation in descriptive essays for class VII students of SMP Jaya Negara. This research is qualitative research. From the results of the research, it shows that students use errors in aspects of emphasis, aspects of thrift, aspects of accuracy, aspects of general guidelines for Indonesian, aspects of logic, and aspects of equivalence. Whereas in punctuation, students also still use a lot of mistakes in placing: full stop error (.), comma error (,), and hyphen error (-). Based on these results, the interpretation of errors in the use of effective sentences and punctuation marks in the descriptive text of class VII SMP Jaya Negara students is: (a) Effective sentences are more dominant in errors in aspects of the general guidelines of the Indonesian language, while (b) Punctuation is more dominant in errors in placing commas (,).